Lagu Ku Kira Kau Rumah Karya Aya Canina: Kajian Intertekstual - ZA, Zaky Adami Adha; Nasution, M. Ismail (Universitas Negeri Padang, 2024)
Aya Canina, in the lyrics of her song titled Ku Kira Kau Rumah, expresses her disappointment towards someone who has come into her life. Initially, this song started as a poem she wrote in 2016, then it was perfected into a song in 2017 by Aya Canina and Isa Maulana Elfasya. This study examines the structural changes in the song Ku Kira Kau Rumah and explores the hypogram form of the song Ku Kira Kau Rumah. The writing method used in this study is a descriptive method, which is conducted by describing an object to provide a depiction of the reality of the object under study, using a qualitative approach. According to Semi (1993:23), qualitative research is carried out by prioritizing depth of understanding of interactions between concepts being empirically studied rather than focusing on numbers. Based on the research conducted, the conclusions are as follows: (1) The structure of the song Ku Kira Kau Rumah by Aya Canina consists of diction (word choice), imagery, concrete words, figurative language, theme, tone, mood, and message. (2) The meaning of the lyrics of the song Ku Kira Kau Rumah by Aya Canina, based on its hypogram, represents the ups and downs and joys and sorrows of the writer in maintaining the hope that has formed in her mind, where over time, this hope gradually fades, resulting in feelings of disappointment that ultimately pour out into the song lyrics.